Rodent-Mediated Seed Dispersal Shapes Species Composition and Recruitment Dynamics in Ecotones - Yu, Fei; Shi, Xiaoxiao; Yi, Xianfeng; Ma, Jianmin (Frontiers in Plant Science, 2018)
Ecotones are considered unique environments, and the concepts of edge effects and ecotonal species have been applied widely. Our understanding of the mechanisms that underlie population and community responses to edge effects has been advanced by recent studies. However, little evidence exists to support an increased density and species richness in ecotones regarding rodent-mediated seed dispersal in response to edge plots between communities. Pinus armandii and Quercus variabilis communities are typical of the Qinling Mountains, China. To elucidate what shapes tree species composition and recruitment dynamics in ecotones, we compared the differences in secondary and tertiary seed dispersal as well as predation in pine and oak by scatter-hoarding rodents as well as the regeneration characteristics of both species in their ecotones with different plots (i.e., 5–8, 15–18, and 27–30 m widths) in the eastern Qinling Mountains. We found that the seeds of pine and oak were removed rapidly, with no differences in the seed removal rates in their ecotones with different plots. Moreover, 13.0 and 36.0% of the scatter hoards of pine and oak, respectively, were established by small rodents in ecotones with a width of 5–8 m, and 3.67 and 7.33% in ecotones with a width of 27–30 m. The seedling densities of pine and oak were significantly higher in ecotones at widths of 5–8 m compared with widths of 15–18 and 27–30 m. According to the seed dispersal and seedling recruitment patterns of pine and oak, the disproportionate abundance of seedlings in ecotones may be due at least partly to patterns of seed caching by rodents.